The Mediating Role of Competitive Advantage in The Relationship Between Capabilities and MSME Sustainability in Bali - I Gusti Agung Prabandari Tri Putri; Desak Putu Nitya Dewi; I Gst. Agung Pramesti Dwi Putri; Gusti Ayu Ratnawati; I Made Dwitya Rastiawan (Indonesian Journal of Business and Entrepreneurship, 2026)
Background: MSME sustainability is a critical for regional resilience in Bali. However, prior studies have not adequately explained how different dimensions of capabilities influence sustainability outcomes through competitive advantage as a mediating.Purpose: This research aims to examine the role of competitive advantage as a mediating variable in the influence of dynamic, management, technological, and innovation capabilities on MSME sustainability in various sectors.Design/methodology/approach: Quantitative data were collected using a questionnaire, with a sample size determined based on a minimum SEM calculation of 5-10 times the number of indicators and research variables. The total sample consisted of 168 MSME owners in Bali, respondents namely MSME owners in Bali, selected through purposive sampling based on predetermined criteria. Data were analyzed using PLS-SEM to examine complex relationship and mediating effects.  Findings/Result: Innovation capability and competitive advantage have a direct and significant effect on MSME sustainability, whereas dynamic, management, and technological capability do not show a significant direct effect. Management and innovation capabilities significantly influence competitive advantage, but only management capability contributes to sustainability through mediation. These findings suggest MSME sustainability is driven more by innovation and competitive positioning than by the development of other capabilities. Conclusion: Sustainable MSMEs can be achieved by improving innovation capabilities and competitive advantage. Competitive advantage functions as a specific mechanism that links management capability to sustainability, suggesting that not all internal capabilities are effectively translated into sustainability outcomes.Originality/value (State of the art): The findings indicate that the impact of capabilities on MSME sustainability is selective, highlighting competitive advantage as a key mediating mechanism in supporting the development of a local product-based economy. Keywords:    sustainable msme, competitive advantage, capabilities, strategic management